The Theological Essence of Human Creation: A Comparative Study Across Perspectives and Its Implication for Human Exixtence - Zerlinda Prasanti Supranggono; Alfaizah Fiddaroini (Kamil : Journal of Education, 2026)
The debate regarding the origins and nature of human existence continues to evolve dynamically in the realms of theology, philosophy, and modern science. This study aims to investigate the nature of the theology of human creation and explore its practical implications for the development of spirituality and human dignity. Using a qualitative method based on library research, this article compares the views of Christian theological anthropology, the discourse of the Qur'anic text in QS. al-Mu'minun: 12-14, and their interrelationship with the theory of evolution of modern science. The results of the study show two main findings. First, the nature of creation affirms that humans are the crown of noble creation, possessing a unity of body, soul, and spirit, and are endowed with responsible free will. Second, theologically, human creation has direct implications for the potential for developing transcendent spirituality, high self-esteem, and essential abilities in determining life choices. This article provides a theoretical contribution to the development of human character in the modern era, which often ignores the essential values ​​of creation.